Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward & Peppard (Studi Kasus : PT Scafol Technology Indonesia) - Dwi Putri, Salsabila An-nisa; Setiawan Assegaff; Benni Purnama (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Information System Strategic Planning (ISSP) is a crucial step for companies to enhance operational efficiency, support business goal achievement, and create a competitive advantage. PT Scafol Technology Indonesia, a company engaged in construction technology, faces challenges in integrating information systems and information technology (IS/IT) to improve business process effectiveness and service quality. Currently, the company still relies on manual processes in several operational aspects, leading to inefficiencies and potential errors in data management and decision-making. Therefore, this study aims to develop a strategic information system plan using the Ward & Peppard method to address the company’s challenges. The results of this study produce an IS/IT strategy blueprint that PT Scafol Technology Indonesia can utilize to optimize business processes and enhance the effectiveness of technology-based construction project management. Information System Strategic Planning (ISSP) is a crucial step for companies to enhance operational efficiency, support business goal achievement, and create a competitive advantage. PT Scafol Technology Indonesia, a company engaged in construction technology, faces challenges in integrating information systems and information technology (IS/IT) to improve business process effectiveness and service quality. Currently, the company still relies on manual processes in several operational aspects, leading to inefficiencies and potential errors in data management and decision-making. Therefore, this study aims to develop a strategic information system plan using the Ward & Peppard method to address the company’s challenges. The results of this study produce an IS/IT strategy blueprint that PT Scafol Technology Indonesia can utilize to optimize business processes and enhance the effectiveness of technology-based construction project management.